Two Species of Thienemanniella Kieffer from Oriental China (Diptera: Chironomidae: Orthocladiinae) - Fu, Yue; Fang, Xiangliang; Wang, Xinhua (Zootaxa, 2013)
A new species from Oriental China, Thienemanniella curva sp. n. is described and illustrated as adult males. T. nipponica which belong to eye bare species group in Thienemanniella from Guangdong Province is re-described. A revised key to known males of the world is provided.